Prevalence of Mental Disorders Among The Students of Jahrom University of Medical Sciences Andits Related Components: Adescriptive, Cross-Sectional Study - navid kalani (Journal of Global Pharma Technology, 2017)
Introduction: Students are the future managers of society. That's why providing their mental health is of particular importance. For this purpose, intensity and grounds of their mental disorder should be examined at different levels of education. Hence, the present paper aims at tackling with the prevalence of mental disorders among the students of Jahrom University of Medical Sciences and its related components.Materials and Methods: This study is a descriptive study conducted to examine the mental disorder among the students of Jahrom University of Medical Sciences. In this study, 214 questionnaires were completed by the freshmen and seniors of four disciplines (medicine, nursing, anesthesiology and operating room technician). Data gathering was done by the two-part questionnaire consisting of demographic information (demographic) and General Health Questionnaire (GHQ-28).Information was analyzed by SPSS statistical software and descriptive statistical tests and t-test.Results: The results showed that 37.7 percentages of people are suspicious in terms of the symptoms. Moreover, the highest level of mental disorders in freshmen was in the scale of anxiety and the lowest level was in the scale of depression. While the highest prevalence of mental disorders in seniors was in the scale of depression and the lowest incidence was in the scale anxiety. Also, no significant relationship was observed among coefficient illness test, gender and age was not a factor of the disease and test. (p> 0/05%).Conclusion: Numerous factors could cause or aggravate some mental disorders in students. Therefore, the authorities are required to take better measures, compared to the past, in the prevention of such disorders. Keywords: Mental health, Students, Public health.